TATA KELOLA ADMINISTRASI DESA DALAM PENYELENGGARAAN PEMERINTAHAN DESA MUNDUNG SATU KECAMATAN TOMBATU TIMUR KABUPATEN MINAHASA TENGGARA - KINDANGEN, INTAN LEVINA; PANGKEY, MASJE; TAMPONGANGOY, DEYSI (Sam Ratulangi University, 2018)
Abstract: This study aims to describe how the implementation of administrative governance in theimplementation of village governance.This research uses qualitative descriptive method, and data collection techniques used are observation,interview and documentation. The number of informants in this study as many as seven people. In this studyusing the theory of basic principles of good governance. The results of this study indicate that in theimplementation of government in the village of Mundung Satu, not all village administrations can be appliedin accordance with applicable regulations that refers to PERMENDAGRI No. 47 of 2016. Lack of toolsneeded to manage village administration, as well as lack of capabilities and government responsibilitiesvillages in implementing their duties, and the implementation of work tasks that are not in accordance withthe main duties and functions of the village apparatus, are the factors behind the implementation of goodadministrative governance. Therefore, the village government should work harder and improve the abilityof village officials to realize good governance and in accordance with the regulations.Keywords: Governance, Village Administration, Village Government Implementation.